Experience With Medical Treatment of Cesarean Scar Ectopic Pregnancy (CSEP) With Local Ultrasound-Guided Injection of Methotrexate - Gerday, Amandine; Lourtie, Amélie; Pirard, Céline; Laurent, Pascale; Wyns, Christine; Jadoul, Pascale; Squifflet, Jean-Luc; Dolmans, Marie-Madeleine; Van Gossum, Jean-Paul; Hammer, Frank; Luyckx, Mathieu (Frontiers in Medicine, 2020)
Objective : Ectopic pregnancy in the site of the cesarean section scar is a rare condition with a significant risk of bleeding and poor prognosis for survival where diagnosis is delayed. To date, there is no consensus on management of this type of ectopic pregnancy. Indeed, different types of treatment may be offered to patients such as medical or surgical treatment, or a combination of both. Patients and Methods This is a retrospective, unicentric study in which we present our findings regarding ultrasound-guided injection of Methotrexate directly into the cesarean section scar in 9 patients, one of whom had a recurrence of pregnancy in the cesarean section scar site. Results : Diagnosis of ectopic pregnancy was made in all cases using transvaginal ultrasound. Half of our patients were asymptomatic at the time of diagnosis. We observe a return to a normal HCG level within 3 months on average without the need for additional therapy (medical or surgical treatment). The pregnancy rate is 50 % after the treatment. Conclusions : Ectopic pregnancy in the cesarean section scar site is a rare condition where early diagnosis is essential to avoid significant risk of bleeding. Local ultrasound-guided injection of Methotrexate into the gestational sac is a safe and effective therapeutic approach when performed by a trained team in the early stage of pregnancy and in a haemodynamically stable patients.